Fast and simultaneous analysis of carbamate pesticides and anticoagulant rodenticides used in suspected cases of animal poisoning. (June 2021) - Gallocchio, Federica; Moressa, Alessandra; Stella, Roberto; Rosin, Roberta; Basilicata, Lara; Bille, Laura; Toson, Marica; Biancotto, Giancarlo; Lega, Francesca; Angeletti, Roberto; Binato, Giovanni
Highlights: Rapid QuEChERS-based analytical method applicable to suspected animal poisonings. Simultaneous identification of carbamate pesticides and anticoagulant rodenticides. Retrospective analysis to detect 15 other compounds outside the scope of the method. Abstract: Carbamate pesticides (CBs) are reported as one of the main causes of intentional or accidental poisoning of animals. Anticoagulant rodenticides (ARs) form the main class of poisons implicated in analyzed poisoned baits. These two groups of pesticide compounds include multiple substances, and thus, the development of a simple and rapid multiclass/multiresidue analytical method for simultaneous identification of both toxicant classes should be a useful strategy for analytical laboratories to reduce analysis time and cost. The present study aimed to elaborate and validate a rapid method to simultaneously determine 11 CBs and 8 ARs in samples of real matrices (bait, stomach content, and liver) from suspected animal poisoning cases. QuEChERS sample treatment and liquid chromatography coupled to hybrid high resolution mass spectrometry were used. The method resulted in good linearity (R 2 ≥ 0.98) for all compounds, recovery was between 70% and 120% for CBs and 40–90% for ARs, and precision was ≤ 20% for all compounds. The method was successfully applied to the analysis of 871 real samples originating from suspected cases of animal poisoning, collected from April 2019 to October 2020. Furthermore, full scan dependent data acquisition allowed qualitative retrospective data analysis of an additional 15 compounds outside the scope of the method to be performed; these compounds could potentially be involved in unresolved poisoning cases.